On the Transmission of Elements of Intangible Cultural Heritage – the Example of the Carnival Rituals in a Rural Environment - Jágerová, Margita (Literatura Ludowa. Journal of Folklore and Popular Culture, 2024)
The carnival (fašiangy) is a long-established and still occurring cultural phenomenon in Slovak society. It resonates not only in our society as a whole, but also at local level as a significant period of the calendar ritual cycle. The contribution presents the problem of the transmission of selected carnival phenomena in the municipality of Borský Mikuláš (the Senica District) in the south-west of Slovakia. Dealing with current ways of transferring the traditional model of the carnival door-to-door sabre procession and maintaining its continuity, as well as current ways of studying carnival rituals and necessary skills, the text draws attention to new ways of using and dealing with these phenomena of intangible cultural heritage in the current rural society.